Economic Empowerment of Micro, Small, and Medium Enterprises (MSMEs) in the Leather Industry through Black Soldier Fly (BSF) Magot Cultivation - Rukmana, Asep Nana; Aviasti, A; Amaranti, Reni; Septiani, Anis (KnE Social Sciences, 2024)
The leather processing industry always experiences growth every year. However, at the stage of processing leather to become raw material for a product, it produces a lot of solid waste containing hazardous materials used during the process. The resulting hazardous materials can cause pollution to the surrounding environment. Hence, there needs to be a solution to handle this solid waste, so that it does not pollute the surrounding environment. Magot Black Soldier Fly (BSF) cultivation training is a technique that can be used as a solution to process solid waste from the leather tanning industry so that it has high selling value. In a study, BSF cultivation shows circular economic results and future opportunities for investors, which will lead to increased demand. The cultivation of BSF as an alternative for processing waste into organic fertilizer and animal feed is a promising technology. It is worth inoculating, especially in countries that have low incomes with expensive fertilizer and animal feed costs. BSF maggot cultivation training was conducted for MSME players in the Sukaregang leather industry in the Garut district. The results of the evaluation were that 99% of the training activity participants felt that the training provided was very targeted and the material provided was appropriate, and easy to understand. So it can be concluded that the training provided is appropriate and beneficial for leather industry MSMEs, whoever participates. Keywords: BSF, economic empowerment, leather industry